DAMPAK PENGGUNAAN METODE BELAJAR SAMBIL BELAJAR PADA PEMBELAJARAN IPS “ Daerahku Kebanggaanku” DI KELAS V SDN 02 TAEH BUKIK KECEMATAN PAYAKUMBUH - Velina Safitri; Ulfa Nabila; viona ramadhani; Zonatul Fajira; Susi Ratna Sari (STKIP Subang, 2026)
The purpose of this study was to determine the effect of the application of Game-Based Learning methods in improving the social skills of fifth-grade elementary school students, especially in learning Social Studies about